2007
DOI: 10.1093/jjco/hym032
|View full text |Cite
|
Sign up to set email alerts
|

Rectum Dose Analysis Employing a Multi-purpose Brachytherapy Phantom

Abstract: The multi-purpose brachytherapy phantom constructed for this study successfully reproduced an optimal dose measured under the same conditions found in actual therapy in which the dose was precisely analyzed at a rectal reference point. In addition, these results were considered reliable and applicable for dose optimization before applying therapy using the measured data from the phantom in order to reduce rectal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The shift could be caused by detector movement between the time of CT scan and irradiation. Rectal peristaltic motion or patient movement has also been reported to affect in-vivo dose measurement (Allahverdi et al, 2012;Allahverdi et al, 2013;Waldhäusl et al, 2005;Huh et al, 2007;Alecu et al, 1999). Many studies have reported significant diode displacement, which has been attributed primarily to being a source of error in performing in-vivo dosimetry in brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The shift could be caused by detector movement between the time of CT scan and irradiation. Rectal peristaltic motion or patient movement has also been reported to affect in-vivo dose measurement (Allahverdi et al, 2012;Allahverdi et al, 2013;Waldhäusl et al, 2005;Huh et al, 2007;Alecu et al, 1999). Many studies have reported significant diode displacement, which has been attributed primarily to being a source of error in performing in-vivo dosimetry in brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Calculation of absorbed dose distribution in a patient before treatment is one of the main steps in treatment planning of radiation therapy. In high-dose-rate (HDR) brachytherapy, the accuracy of calculation becomes an important issue because of the higher dose rate and prescribed dose per session [ 5 , 6 ]. Thus, inaccuracies in dose distribution measurement may lead to higher dose to healthy tissues or lower dose to the tumor.…”
Section: Purposementioning
confidence: 99%
“…Of patients who receive radiotherapy, 3–10% experience rectum and bladder sequelae such as proctitis, cystitis, and fistule 6 . The incidence rate increases with an increasing dose per fraction 7 8 .…”
mentioning
confidence: 99%